Core-Shell-Structured Particle Reinforced A356 Matrix Composite Prepared by Powder-Thixoforming: Effect of Reheating Temperature - Chen, Tijun; Geng, Libo; Qin, He; Gao, Min (Materials, 2018)
A novel core-shell-structured Ti-(Al-Si-Ti) particle (Ti-(Al-Si-Ti)p) reinforced A356 matrix composite was fabricated by a new method, powder thixoforming, which combines the merits of both powder metallurgy and semisolid thixoforming. The effects of reheating temperature on the microstructure and tensile properties of the resulting composite were investigated. The results indicated that the thickening of the Al-Si-Ti compound shells, with rising the reheating temperature, significantly enhanced the strengthening role, but the fracture and peeling of the shells, at higher than 600 °C, impaired the strengthening effect. The composite formed at 600 °C had a favorable tensile elongation of 8.3% besides high tensile strengths. During tensile testing, the Ti@(Al-Si-Ti)p frequently fractured across the Ti cores and occasionally cracked around the Ti cores, but preferentially fractured between the outer cracked shells and the inner cores for the composites thixoformed at higher than 600 °C. The delayed formation of cracks in the Ti-(Al-Si-Ti)p and the small size of the cracks contributed to ductility improvement. The MSL model, modified according to the Ti@(Al-Si-Ti)p characteristics, was essentially suitable for predicting the yield strength of such composites. The largest contribution to the strength was resulted from solid solution strengthening of Ti element, but the strengthening role from geometrically necessary dislocations was significantly improved as the reheating temperature rose from 590 °C to 600 °C.